The visual cognitive network, but not the visual sensory network, is affected in amnestic mild cognitive impairment: A study of brain oscillatory responses - Yener, Görsev; Emek Savaş, Derya Durusu; Güntekin, Bahar; BAŞAR, EROL (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2014)
Mild Cognitive Impairment (MCI) is considered in many as prodromal stage of Alzheimer's disease (AD). Event-related oscillations (ERO) reflect cognitive responses of brain whereas sensory-evoked oscillations (SE) inform about sensory responses. For this study, we compared visual SEO and ERO responses in MCI to explore brain dynamics (Background). Forty-three patients with MCI (mean age=74.0 year) and 41 age- and education-matched healthy-elderly controls (HC) (mean age=71.1 year) participated in the study. The maximum peak-to-peak amplitudes for each subject's averaged delta response (0.5-3.0 Hz) were measured from two conditions (simple visual stimulation and classical visual oddball paradigm target stimulation) (Method). Overall, amplitudes of target ERO responses were higher than SEO amplitudes. The preferential location for maximum amplitude values was frontal lobe for ERO and occipital lobe for SEO. The ANOVA for delta responses showed significant results for the group Xparadigm. Post-hoc tests indicated that (1) the difference between groups were significant for target delta responses, but not for SEO, (2) ERO elicited higher responses for HC than MCI patients, and (3) females had higher target ERO than males and this difference was pronounced in the control group (Results). Overall, cognitive responses display almost double the amplitudes of sensory responses over frontal regions. The topography of oscillatory responses differs depending on stimuli: visualsensory responses are highest over occipitals and -cognitive responses over frontal regions. A group effect is observed in MCI indicating that visual sensory and cognitive circuits behave differently indicating preserved visual sensory responses, but decreased cognitive responses (Conclusion). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Oscillations; Event-related; Mild cognitive impairment; MCI; Alzheimer; P300; Dementia; Event-Related Oscillations; Alzheimers-Disease; Delta; Biomarkers; Scale; Theta; Eeg; Electroencephalography; Potentials; Diagnosis